Learners' epistemic criteria and strategies for evaluating scientific visual representations. (December 2018) - Barzilai, Sarit; Eilam, Billie
Abstract: Visual information sources are increasingly available online, yet little is known about how learners evaluate such information sources. Hence, the purpose of this study was to document learners' epistemic criteria and strategies for evaluating scientific visual representations (VRs). Junior high-school students evaluated four pairs of VRs that included different representations of the same phenomenon, justified their judgements, and described their criteria and strategies for evaluating good scientific VRs. Learners described and applied criteria related to the representation of the referent, to communicative quality, and to affordances for achieving epistemic aims, such as understanding. Learners applied criteria adaptively: Design contrasts between VRs evoked greater use of communicative and epistemic aim affordance criteria, whereas informational contrasts evoked greater use of representational criteria. Learners described a range of VR evaluation strategies. However, only a minority mentioned information validity and source trustworthiness evaluation strategies. Implications regarding learners' epistemic competence for evaluating VRs are discussed. Highlights: We examined learners' epistemic criteria and strategies for evaluating visual representations. Representational, communicative, and epistemic aim affordance criteria were described and used. Design contrasts between VRs evoked more communicative and epistemic aim affordance criteria. Informational contrasts between VRs evoked more representational criteria. Strategies for evaluating information and source trustworthiness were infrequently described.